STATUS GIZI, KEBIASAAN SARAPAN PAGI DAN KELELAHAN KERJA PADA PEKERJA KAPAL CEPAT (FAST FERRY) PT. BALI EKAJAYA - LINA YUNITA; NI MADE WIASTY SUKANTY; NOVIANTI TYSMALA DEWI; FARIDA ARIANI (GANEC SWARA, 2023)
Fatigue is mental or physical fatigue that makes it difficult for a person to work comfortably and effectively. One of the factors contributing to reducing the level of work fatigue is by fulfilling worker nutrition so as to improve health. The risks of burnout include work-related stress, work-related illnesses and work-related accidents. This study aims to analyze the relationship between nutritional status, breakfast habits and work fatigue among employees of fast ferry shipping companies. This type of research used an analytic survey with a cross sectional study approach. This research was carried out at Sengig Port, West Lombok Regency, Nusa Tenggara. The sample of this research is the entire crew of the three fast boat fleets with a total of 41 samples. The research variables are nutritional status, breakfast habits and work fatigue. Nutritional status data is obtained by directly measuring body weight and height. Breakfast data was obtained by interviewing using a 24-hour recall form. Fatigue data was obtained using a fatigue questionnaire. The results showed that most of the workers used to have breakfast, almost 68.3%. Respondents who had normal nutritional status were 51.2% and workers who experienced mild fatigue were 58.5%. Statistical test results for breakfast with nutritional status obtained p = 0.01, statistical tests for breakfast with fatigue obtained p = 0.23, and statistical test results for nutritional status with fatigue obtained p = 0.37. there is a relationship between breakfast, nutritional status and fatigue in workers but there is a relationship between breakfast habits and nutritional status in fast boat company employees at Senggigi port